SHP2 Nuclear/Cytoplasmic Trafficking in Granulosa Cells Is Essential for Oocyte Meiotic Resumption and Maturation - Idrees, Muhammad; Kumar, Vikas; Joo, Myeong-Don; Ali, Niaz; Lee, Keun-Woo; Kong, Il-Keun (Frontiers in Cell and Developmental Biology, 2021)
Src-homology-2-containing phosphotyrosine phosphatase (SHP2), a classic cytoplasmic protein and a major regulator of RTK and GPCRs, plays a significant role in preimplantation embryo development. In this study, we deciphered the role of SHP2 in the somatic compartment of oocytes during meiotic maturation. SHP2 showed nuclear/cytoplasmic localization in bovine cumulus and human granulosa (COV434) cells. FSH treatment significantly enhanced cytoplasmic SHP2 localization, in contrast to the E2 treatment, which augmented nuclear localization. Enhanced cytoplasmic SHP2 was found to negatively regulate the expression of the ERα-transcribed NPPC and NPR2 mRNAs, which are vital for oocyte meiotic arrest. The co-immunoprecipitation results revealed the presence of the SHP2/ERα complex in the GV stage COCs, and this complex significantly decreased with the progression of meiotic maturation. To support our findings, the probable binding mode between ERα and SHP2 was identified using a series of computational modeling methods. To verify the correlation between SHP2 and NPPC/NPR2, SHP2 was knocked down via RNA interference (RNAi), and NPPC and NPR2 mRNAs were analyzed in the control, E2, and FSH-stimulated COV434 cells. Furthermore, PHPS1 a site-directed inhibitor of active SHP2 showed no significant effect on the ERα-transcribed NPPC and NPR2 mRNAs. Taken together, these findings support a novel nuclear/cytoplasmic role of SHP2 in oocyte meiotic resumption and maturation.